Traversing educational deserts: a community case study of technical STEMM pathways in Wyoming’s rural remote transfer ecosystem - McBride, Rosemary (Frontiers in Education, 2025)
Across Wyoming’s remote educational landscapes, rural technical STEMM educators (RTSEs) engage in complex relational work supporting student navigation through challenging institutional, cultural, and physical barriers. Through analysis of lived experiences shared by 42 RTSEs across eight counties, this community case study reveals how successful rural STEMM education emerges through integrated supports addressing mental health needs, family dynamics, and cultural contexts while building vital technical skills. Evidence demonstrates RTSEs operate simultaneously across geographic, economic, and demographic dimensions—bridging between local knowledges and broader academic systems. Key findings highlight the importance of relationship-centered approaches that honor rural contexts while addressing universal challenges. Recommendations include developing coordinated support networks and expanding industry-education partnerships grounded in local community needs.